Central and peripheral modulation of gastrointestinal transit in mice by DN‐9, a multifunctional opioid/NPFF receptor agonist. Issue 8 (12th April 2020) - Xu, Biao; Guo, Yuanyuan; Zhang, Mengna; Zhang, Run; Chen, Dan; Zhang, Qinqin; Xiao, Jian; Xu, Kangtai; Li, Ning; Qiu, Yu; Zhu, Hanwen; Niu, Jiandong; et al.
Abstract: Background: The nonapeptide DN‐9 functions as a multifunctional agonist to opioid and neuropeptide FF (NPFF) receptors and exhibits antinociceptive effects at the central and peripheral levels. Methods: The effects of DN‐9 on small and colonic intestinal transit were evaluated using the upper gastrointestinal (GI) transit test and colonic bead expulsion assay, respectively. Opioid and NPFF receptor antagonists were used to investigate the mechanisms of DN‐9‐induced GI inhibition. Furthermore, the agonism of the DN‐9 analog [Phg 9 ]‐DN‐9 to opioid and NPFF receptors was tested by the cAMP assay. Key results: Intracerebroventricular administration of DN‐9 dose‐dependently slowed upper GI transit and colonic expulsion via mu‐ and kappa‐opioid receptors in the brain, independent of the delta‐opioid receptor. Similarly, intraperitoneal injection of DN‐9 dose‐dependently inhibited GI propulsion via the peripheral opioid receptors. DN‐9‐induced GI transit inhibitions were significantly aggravated by the NPFF receptor antagonist RF9. Moreover, the DN‐9 analog [Phg 9 ]‐DN‐9, an agonist at mu‐, delta‐, and kappa‐opioid receptors but not NPFF receptors, inhibited GI more potently than DN‐9. In addition, intracerebroventricular NPFF significantly attenuated the central inhibitory effects induced by [Phg 9 ]‐DN‐9 and morphine. However, central and peripheral injections of NPFF or RF9 almost had no significant effects on GI transit by itself. Conclusion and Inferences: Intracerebroventricular and intraperitoneal administrations of DN‐9 inhibit GI transit via opioid receptors in mice by central and peripheral mechanisms, respectively. In addition, the NPFF agonism of DN‐9 possesses antiopioid effects on GI transit, which might explain the reduced constipation at the antinociceptive doses. Abstract : Central and peripheral administrations of the novel opioid/NPFF receptor agonist DN‐9 exhibit reduced gastrointestinal transit inhibition compared with that of morphine. Our data provide some insight into multifunction analgesic research as well as the development of peripherally acting opioids.